Risk‐Based Decision‐Support Groundwater Modeling for the Lower San Antonio River Basin, Texas, USA. Issue 4 (13th May 2021) - Foster, Linzy K.; White, Jeremy T.; Leaf, Andrew T.; Houston, Natalie A.; Teague, Aarin
Abstract: A numerical surface‐water/groundwater model was developed for the lower San Antonio River Basin to evaluate the responses of low base flows and groundwater levels within the basin under conditions of reduced recharge and increased groundwater withdrawals. Batch data assimilation through history matching used a simulation of historical conditions (2006‐2013); this process included history‐matching to groundwater levels and base‐flow estimates at several gages, and was completed in a high‐dimensional (highly parameterized) framework. The model was developed in an uncertainty framework such that parameters, observations, and scenarios of interest are envisioned stochastically as distributions of potential values. Results indicate that groundwater contributions to surface water during periods of low flow may be reduced from 6% to 25% with a corresponding 25% reduction in recharge and a 25% increase in groundwater pumping over an 8‐year planning period. Furthermore, results indicate groundwater‐level reductions in some hydrostratigraphic units are more likely than in other hydrostratigraphic units over an 8‐year period under drought conditions with the higher groundwater withdrawal scenario.